Ketegangan HAM dan Hukum Islam: Menelusuri Akar Masalah - Moh Munir (Justicia Islamica, 2007)
This study aims to explore the root of the tension between human rights and Islamic law. It explores the main sources of disagreement between universal human rights principles and Islamic legal norms, as well as attempts at reconciliation between the two. The method used is library research with a descriptive-analytical approach. The research sources include international legal documents, classical and contemporary Islamic legal literature, and related academic studies. The results of the study show that this tension is rooted in epistemological differences, historical contexts, and legal interpretations that have developed in various Muslim regions. Despite these differences, a number of modern Muslim thinkers have attempted to harmonize human rights and Islamic law. This study emphasizes the importance of constructive dialogue to bridge differences without neglecting the fundamental principles of each legal system.